Effects of leadership types on job satisfaction among Malaysian higher education institutions - Shaari, R.; Kamarudin, D.; Soon-Yew, J.; Zakaria, H. (Asya Öğretim Dergisi, 2022)
Employee job satisfaction is an important component of any job and could be influenced by different types of leadership. Keeping employees happy and satisfied while at the same time being a great leader is an extremely difficult balance, especially in educational leadership, where there are two different types of employees, mainly administrators, and educators. It requires a leader who can balance between the lines and choose the proper leadership style to motivate different types of employees. This study looks at three different leadership types: laissez-faire, transformational and transactional leadership. A purposeful sampling of 393 participants was utilized to sample educators from Malaysia's private and governmental education institutions. Data were collected using questionnaires. The findings indicated that transformational leadership and laissez-faire have a significant relationship to job satisfaction where laissez-faire (β = 0.608, t = 16.576, p = 0.000) and transformational leadership (β = 0.865, t = 8.498; p = 0.000), while transactional leadership has an insignificant relationship with job satisfaction (β = -0.019, t = 0.747, p = 0.227).